Mechanisms for Developing Sociometric Relationships Between Teachers and Students - R. G. Safarova , (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2026)
Teacher–student sociometric relationships represent an important dimension of the educational process, influencing classroom climate, academic achievement, social adaptation, emotional well-being, and students’ sense of belonging. Contemporary educational research increasingly recognizes that positive teacher–student relationships contribute significantly to learning effectiveness and psychosocial development. The present study aims to examine the historical evolution, theoretical foundations, methodological approaches, and contemporary educational implications of sociometric relationships between teachers and students. A qualitative research design based on systematic literature review and comparative analysis was employed. Scientific sources from sociometry, educational psychology, social-emotional learning, attachment theory, and restorative practices were analyzed. The findings reveal that teacher–student sociometric relationships have evolved from classical sociometric concepts of interpersonal choice and rejection toward multidimensional frameworks encompassing trust, emotional support, fairness, inclusion, and psychological safety. The study highlights the importance of integrating sociometric, humanistic, socio-constructivist, social-emotional learning, and restorative approaches in modern educational environments. The results suggest that systematic development of sociometric relationships contributes to improved educational outcomes, enhanced classroom climate, and greater student well-being.